Sense of Coherence and Physical Health. Testing Antonovsky's Theory - Trine Flensborg-Madsen; Søren Ventegodt; Joav Merrick (The Scientific World Journal)
In a previous paper, we argued that the original 29-item sense of coherence (SOC) scale developed by Aaron Antonovsky (1923–1994) was insufficient according to its reflection of SOC. The purpose of this study was to create a new version of the original 29-item SOC scale in order to test his hypothesis of a causal link between SOC and physical health. This shorter version was built on the exact same idea, theory, and conceptualization used by Antonovsky, which resulted in a SOC scale containing only 9 abstract questions. These nine questions, in addition to two questions about physical and psychological health, made up a questionnaire answered by 100 people at the entrance hall of the University Medical Center (Rigshospitalet) in Copenhagen. According to Antonovsky’s famous hypothesis, a strong association should be found between SOC and physical health, but surprisingly, we found that the new scale was falsifying the hypothesis, with a correlation between SOC and physical health of only r = 0.044 (NS). However, a highly significant correlation was found with psychological health with r = 0.502 (p = <0.0005). The authors are in a predicament since we strongly believe in Antonovsky’s famous idea of the relationship between SOC and health. However, we believe that it is our emotional aspects that primarily determine our physical health, which we will demonstrate in a subsequent study, but the reason we did not find any significant correlation in this study was the fact that our nine-item SOC scale was very mental (mental in the sense of applying to conscious cognition and attitude). We consider the mental aspects to determine our psychological health and the emotional aspects to determine our physical health. Our conclusion is that the original 29-item SOC scale mixed a few emotional aspects into the otherwise mental construct, which is the reason for the relatively low correlations found until now, when using the original scale.